Analisis Rasio Keuangan terhadap Struktur Modal (Perusahaan Makanan dan Minuman di BEI 2015-2018) - Melia Sari (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2020)
Capital structure is a picture of a company's finances that is a source of discussion within the company. This study discusses to analyze and analyze the financial ratio analysis of the Capital Structure of the food and beverage subsector companies listed on the Indonesia Stock Exchange (BEI) in 2015-2018. The population in this study are food and beverage companies listed on the Indonesia Stock Exchange (BEI) in 2015-2018 using purposive sampling techniques, obtained 12 companies that meet the sample criteria. The method used is multiple linear regression. The results of this study indicate that profitability, liquidity, and asset structure affect the capital structure. While company size, company growth, and business risk did not increase on capital structure.